Thirty years onward! Citation analysis of randomized experiments on drug and mental health courts - Sloas, Lincoln B. (Journal of experimental criminology, 2020)
This study is meant to conduct the first known citation analysis on problem-solving courts (PSCs) using experimental designs. The use of citation analysis is meant to contribute to the experimental literature base by investigating the concept of “research quality.”